Leveraging the impact of 360-degree feedback - Fleenor, John W. (Pfeiffer essential resources for training and HR professionals., 2008)
Leveraging the Impact of 360-Degree Feedback is a hands-on guide for implementing and maintaining effective 360-degree feedback as part of learning and development initiatives. Written for professionals who work inside organizations and for consultants.